2016
DOI: 10.3390/ijms17040498
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Modulates TREM-1 Signal Pathway to Inhibit the Inflammatory Response in Rheumatoid Arthritis

Abstract: Triptolide (TP), an active component isolated from Tripterygiumwilfordii Hook F, has therapeutic potential against rheumatoid arthritis (RA). However, the underlying molecular mechanism has not been fully elucidated. The aim of this study is to investigate the mechanisms of TP acting on RA by combining bioinformatics analysis with experiment validation. The human protein targets of TP and the human genes of RA were found in the PubChem database and NCBI, respectively. These two dataset were then imported into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
65
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(67 citation statements)
references
References 39 publications
2
65
0
Order By: Relevance
“…TREM-1 activation can amplify TLRs and NLRs signaling to promote the production of pro-inflammatory cytokines, degranulation of neutrophils, and phagocytosis 111213. Depletion or blocking TREM-1 has shown protective effects in sepsis, ischemia-reperfusion, pancreatitis, inflammatory bowel diseases, Fungal Keratitis and arthritis14151617181920. Our previous study found that the expression of TREM-1 in LPS-induced ALI mice lung and macrophages are significantly increased, suggesting an important role of TREM-1 in ALI2122.…”
mentioning
confidence: 99%
“…TREM-1 activation can amplify TLRs and NLRs signaling to promote the production of pro-inflammatory cytokines, degranulation of neutrophils, and phagocytosis 111213. Depletion or blocking TREM-1 has shown protective effects in sepsis, ischemia-reperfusion, pancreatitis, inflammatory bowel diseases, Fungal Keratitis and arthritis14151617181920. Our previous study found that the expression of TREM-1 in LPS-induced ALI mice lung and macrophages are significantly increased, suggesting an important role of TREM-1 in ALI2122.…”
mentioning
confidence: 99%
“…Accumulating evidence has indicated that TREM1 is an amplifier of the inflammatory process, while TREM2 has anti-inflammatory activity (22,26,28,29). Inhibition of TREM1 has shown to attenuate the inflammation in several animal models of diseases, such as fatty liver diseases, rheumatoid arthritis or pneumonia (28,30,31). Our current study has shown that the three mitochondrial ETC inhibitors significantly decreased both the mRNA and protein levels of TREM1 in LPS-treated BV2 microglia, suggesting that the mitochondrial ETC inhibitor-produced suppression of the LPS-induced microglial activation results at least partially from its capacity to decrease the TREM1 level.…”
Section: Discussionmentioning
confidence: 99%
“…The current researches on the mechanism of TPL in the treatment of RA mainly includes the following aspects: Wang et al () applied TPL to collagen‐induced RA mice, suggesting that TPL could improve arthritis symptoms of RA by inhibiting the secretion of inflammatory cytokines by T lymphocytes; Kong et al () proposed that TPL could inhibit the inflammation of RA by blocking the angiogenesis at the inflammatory site; Su, Sun, Ao, and Zhao () proposed that TPL could mediate the apoptosis of fibroblast‐like synoviocytes and inhibit their inflammation to improve the symptoms of RA. Fan et al () found that TPL could inhibit the degree of inflammation through TREM‐1 signaling pathway; Liu et al () proposed that TPL could block RANKL/RANK/OPG signaling pathways in collagen‐induced RA mice to prevent the formation of OCs from OCPs, thereby inhibiting bone destruction of RA. However, some studies have shown that RANKL inhibitors were unable to prevent the formation of RA or significantly improve its clinical symptoms (Ferrari‐Lacraz & Ferrari, ).…”
Section: Discussionmentioning
confidence: 99%